The Impact of Acute Ammonia Nitrogen Stress on the Gill Tissue Structure and Antioxidant Ability of Gills and Red and White Muscle in Juvenile Yellowfin Tuna (Thunnus albacares) - Yongyue Sun; Zhengyi Fu; Xuancheng Liu; Zhenhua Ma (MDPI AG, 2024)
To explore the impacts of acute ammonia nitrogen (NH3-N) stress on gill structure and the antioxidant ability of red and white muscles in juvenile yellowfin tuna (Thunnus albacares), this study used natural seawater as a control, establishing two experimental NH3-N groups at 5 and 10 mg/L. Gills and red and white muscle were taken at 6, 24, and 36 h for the determination of malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GHS-PX) levels, and to observe gill structure. The results indicated that, with increasing time, the MDA concentration and CAT activity in the gills of the 5 mg/L group showed a trend of first increasing and then decreasing, while SOD activity exhibited a downward trend. In the 10 mg/L group, MDA concentration showed an increasing trend, while SOD, CAT, and GSH-PX activities demonstrated a trend of first increasing and then decreasing. In the 5 mg/L group, the MDA concentration and GSH-PX activity in the red muscle showed an increasing trend. In the 10 mg/L group, MDA concentration and SOD and CAT activities exhibited a downward trend. In the 5 mg/L group, the MDA concentration and SOD activity in the white muscle showed a downward trend, while CAT activity exhibited an increasing trend. In the 10 mg/L group, MDA concentration and CAT activity demonstrated a trend of first increasing and then decreasing, while SOD activity showed a downward trend. Ammonia nitrogen can lead to necrosis and shedding of gill epithelial cells, cell vacuolation, edema, as well as proliferation, hypertrophy, and fusion of secondary lamellae. This study demonstrates that NH3-N can alter gill structure and reduce the antioxidant ability of gills and red-white muscle. The findings provide scientific data that can support the aquaculture and recirculating aquaculture systems of juvenile tuna.